The Influence of Host Attractiveness and TV Programs on Interest in Watching Net.Tv (Case Study of Desta in the Main Hakim Sendiri) - Surianto Surianto; Freddy Denis Khang (Jurnal Syntax Admiration, 2024)
The purpose of this study was to determine the attractiveness of Desta and the ‘Main Hakim Sendiri' program had an effect on viewing interest. This study used quantitative-survey method. Survey research method is a type of method carried out by obtaining factual, actual, and systematic information on certain population facts. The survey also obtained information from some respondents who are representative of a population. The research was carried out in the Jabodetabek area so that the wide reach made it easier for researchers to be able to research people who knew the ‘Main Hakim Sendiri ' program. The population taken in this study is in the form of Indonesian people, both men and women and live in Jakarta, Bogor, Depok, Tangerang, or Bekasi with an infinite number. The results of the T test (partial) show that the variables "host attractiveness" (X1) and "tv program" (X2) significantly positively affect viewing interest (Y), which means that the more attractive Desta is as a host and the better the quality of television programs, the higher the audience's interest in watching. In addition, the results of the F test (simultaneous) also revealed that the two variables simultaneously had a significant positive effect on viewing interest, so the hypothesis that "host attractiveness" and "tv program" had a significant positive effect on viewing interest was accepted, while the opposite hypothesis was rejected.